Pemanfaatan Google Maps Untuk Optimalisasi Pemetaan Lokasi Usaha Warga Dalam Meningkatkan Akses Dan Promosi - Ayu Firdayanti; z, Zuriana; Septarina, Linda (Jurnal Pengabdian Masyarakat Tapis Berseri (JPMTB), 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in driving national economic growth, improvingcommunity welfare, and creating new employment opportunities. MSMEs also contribute significantly to regional economies,particularly in rural areas. However, many MSME actors still face various challenges, especially in adopting technology anddigitalization processes, which limit market access and product promotion. This community empowerment activity aims toassist the digital transformation of Snack dan Cemilan Nda Gemoy, an MSME located in Rawi Village, PenengahanDistrict, South Lampung Regency, through the utilization of Google Maps as a tool for business mapping, promotion, andaccessibility enhancement. The implementation method includes field observation to identify existing problems, technicalassistance in creating and verifying the business location on Google Maps, and training on managing digital information suchas updating operating hours, contact details, and product photos. The results show that the MSME now has an officiallyregistered business location on Google Maps, making it easier for consumers to find the address and recognize the productsoffered. In addition to improving online visibility, this initiative has positively impacted consumer trust, market reach, andthe professional image and legitimacy of the business. Therefore, the use of Google Maps has proven to be an effective andsustainable step in supporting MSME digitalization toward greater independence and competitiveness in the digital era.